AN ERROR ANALYSIS ON THE USE OF SIMPLE PAST TENSE IN NARRATIVE TEXT MADE BY SENIOR HIGH SCHOOL STUDENTS - Fatmawaty, Riryn; Faridah, Fita; Damayanti, Fitria Alifia (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2025)
An Error Analysis on the Use of Simple Past Tense in Narrative Text Made by Senior High School Students at MAN 1 Lamongan (A Descriptive Research). Under the research of the English Education Department, the Faculty of Teacher Training and Education, Lamongan Islamic University.This research aimed to discover the errors on using simple past tense in narrative text made by Senior High School students. The method of this research was descriptive research. The population of this research was the first grade of Senior High School at MAN 1 Lamongan. The sample consisted of 24 students taken from eight class, in Academic Year 2022/2023. The data were collected through the students’ worksheets. The findings of this research indicated that there were 98 total errors that students made which were classified into four categories based on the surface strategy taxonomy. Those were errors of omission with 76 errors, errors of addition with 3 errors, misformation with 15 errors, and misordering with 3 errors. The students made the dominant error in the omission category. It can be seen from the percentage result where omission was 80%, then followed by error of addition with 3%, error of misformation with 14%, and misordering with 3%. Based on the findings, it can be concluded that the first-grade Senior High School at MAN 1 Lamongan had many errors in writing narrative text, especially in using simple past tense. For the next researcher, hopefully, this research can be useful as their reference to conduct other research in different aspects of grammar